EVALUATION OF THE TOLERANCE OF RICE (ORYZA SATIVA) FOR SUBMERGENCE AND DROUGHT USING VARIOUS YIELD RELATED STRESS INDICES - AMJAD, I; KASHIF, M; AKHTAR, S; NAZAR, MZK; LATIF, A; LATIF, A; SARFRAZ, S; SHAHBAZ, U; AHSAN, MT; SHAMIM, F; et al. (Biological and Clinical Sciences Research Journal, 2022)
Rice genotypes were evaluated under submergence stress and drought stress in two separate field conditions under Split Plot design consisting of water stress as the main plots, and rice genotype as the sub-plot treatments. Grain yields under non-stress and stressed conditions were used to calculate stress indices. In the first experiment, four rice genotypes (Swarna Sub1, Ciherang Sub1, IR-07-F289 Sub1 and IR-44 Sub1) along with two high yielding local varieties (KSK-133 and Super Basmati) were evaluated under submergence stress in field conditions. Submergence stress was applied at tillering stage for 21 days. Results of stress indices under submergence revealed that yield stability index was the only stress index which showed strong and positive correlation with crop yield under submergence. Biplot graph exhibited that harmonic mean, geometric mean productivity, mean productivity; stress tolerance index and yield index were the best stress indices among all other indices to identify submergence tolerant genotypes. Based on the stress indices and their correlation results, the genotypes can be classified in different groups. Super Basmati performed well under submergence and normal conditions, KSK-133 performed well under normal conditions, IR-44 Sub1 and Swarna Sub1 performed well under submerged conditions. While in the second experiment drought stress was applied for 30 days on four Sub1 genotypes along with Nagina-22 (Drought tolerant check) and IR-64 (drought susceptible check). Harmonic mean and yield index showed strong positive correlation with the yield under drought stress. Biplot graph exhibited that mean productivity, tolerance index, and stress susceptibility index were the best stress indices among all other indices to identify drought tolerant genotypes. Based on the stress indices and their correlation results it was observed that Nagina-22 performed well under drought and normal conditions, IR-64 performed well only under normal conditions, Swarna Sub1 and IR-07-F289 performed well under drought as compare to the normal conditions. As a whole, the findings of this study indicate that classification and selection of superior genotypes under severe stress conditions is more reliable by using stress indices as a base for selection.